Stimulation of tyrosine phosphatase and inhibition of cell proliferation by somatostatin analogues: mediation by human somatostatin receptor subtypes SSTR1 and SSTR2. - Buscail, L (1994)
The effects of somatostatin analogues RC-160 and SMS-201-995 on tyrosine phosphatase and cell proliferation were investigated in COS-7 and NIH 3T3 cells expressing human somatostatin receptor subtype 1 or 2 (SSTR1 or SSTR2). Binding experiments were performed on membranes from COS-7 cells expressing human SSTR1 or SSTR2 using 125I-labeled [Tyr11]S-14 or [Tyr3]SMS-201-995, respectively. The somatostatin analogues RC-160 and SMS-201-995 exhibited low affinity for SSTR1 (IC50 of 0.43 and 1.5 microM, respectively) and high affinity for SSTR2 (IC50 of 0.27 and 0.19 nM). Addition of these analogues to cells expressing either SSTR1 or SSTR2 did not result in an inhibition of adenylate cyclase activity. In SSTR2-expressing cells, both analogues induced a rapid stimulation of a tyrosine phosphatase activity (EC50: RC-160, 2 pM; SMS-201-995, 6 pM) and an inhibition of serum-stimulated proliferation (EC50: RC-160, 6.3 pM; SMS-201-995, 12 pM). In SSTR1-expressing cells, only RC-160 induced stimulation of a tyrosine phosphatase activity. Both analogues caused an inhibition of cell proliferation at a concentration higher than 10 nM in accordance with their affinities for the SSTR1 receptor subtype. A good correlation between the affinities of RC-160 and SMS-201-995 for each receptor subtype and their potencies to inhibit cell proliferation suggests the involvement of these receptors in cell growth regulation. Tyrosine phosphatase was stimulated by both these analogues in SSTR2 and by RC-160 in SSTR1 at affinities similar to their ability to inhibit growth and bind to receptors, implicating tyrosine phosphatase as a transducer of the growth inhibition signal. We also found that mRNAs of receptor subtypes were variably expressed in different pancreatic and colon cancer cell lines, indicating the necessity of a precise analysis of receptor subtypes in target tissues before therapy with analogues.